DEVELOPMENT AND TESTING OF A SOLAR ADSORPTION REFRIGERATOR UNDER HAZY CONDITION - Abur, Benjamin Ternenge; Waziri, Abudharr Bello; Duvuna, Gideon Ayuba; Oguche, Emmanuel Enemona; Onyema, Abams; Shammah, Innocent Micah; Julius, Eze Ekene (FUDMA Journal of Sciences, 2025)
Preservation of foods, drinks, fruits, fish, and perishables using cleaner form of energy at low financial cost has necessitated the adoption of solar powered refrigeration system most especially in locations with known viable solar resources. A 0.36m 2 solar-powered adsorption refrigeration system utilizing an activated carbon/methanol pair was developed, tested, and evaluated under a cloudy sky condition of harmattan haze of Bauchi weather condition in January. A single 4mm plane glass forms the collector employing the location latitude as the inclination angle. Copper tubes arranged in parallel and connected to two headers are embedded underneath the absorber and, then coated with black paint. Collector air tightness is improved by the use of glazing rubber. Five liters of water in the cooling cabinet attained 13°C after 56 hours of experiment achieving a 41% temperature reduction and, 0.56 cooling coefficient of performance. This work indicates the practicability of solar adsorption refrigeration in the tropics amidst cloudy sky conditions. For improved performance under unfavorable weather conditions, provision should be made for auxiliary heating. The applications of this form of refrigeration will curb the use of conventional energy, minimize grid dependence, reduce household recurrent bills, and ozone layer-depleting chlorofluorocarbons (CFCs).